2023
DOI: 10.4081/jphia.2023.2572
|View full text |Cite
|
Sign up to set email alerts
|

Family perspectives on severe mental disorders and relapse prevention: a qualitative study

Abstract: Background. The relapse of severe mental disorders is still quite high due to the lack of family knowledge in treating schizophrenic patients. The family treats and prevents the relapse of severe mental disorder by taking the sufferer to spiritual treatment, a shaman, being shackled (pasung) because of the assumption that the cause is evil from ghosts, magic, curses, and unbelief. Objective. The purpose of this study is to explore the experience of families preventing the relapse of severe mental disorders. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Stigma means that the family faces psychological, social, and intrapersonal consequences. This decreases the quality of family life and family functionality, and there are opportunities that have a negative impact on family resilience [6], [8].…”
Section: Indonesian Nursing Journalmentioning
confidence: 99%
“…Stigma means that the family faces psychological, social, and intrapersonal consequences. This decreases the quality of family life and family functionality, and there are opportunities that have a negative impact on family resilience [6], [8].…”
Section: Indonesian Nursing Journalmentioning
confidence: 99%
“…For participants and other people faced with similar situations, building and nurturing ties within the community can be a crucial source of support. Similarly, a study by (Sawab et al, 2023) revealed that caregivers of individuals with schizophrenia may experience feelings of helplessness and burden due to a lack of understanding about the care and treatment of severe mental disorders within their families, as well as the absence of social support from their communities. Another study in Surabaya, Indonesia, depicted that providing psychoeducation to the patient's family about schizophrenia and the importance of medication adherence is crucial for the patient's long-term well-being.…”
Section: Care In the Familymentioning
confidence: 99%